Monetary Policies, Banking Systems, Regulatory Convergence, Efficiency and Growth in the Mediterranean - Ayadi, Rym. (Palgrave Macmillan Studies in Banking and Financial Institutions, 2014)
Monetary Policy, central banking, and international norms and regulations; a discussion far from new, nor applying exclusively to the world's most advanced economies. A sound monetary policy and a well-enforced regulatory regime is provided, in explanation of developing nations to channel financial resources more efficiently into investments.